2003
DOI: 10.1103/physrevd.68.014017
|View full text |Cite
|
Sign up to set email alerts
|

Study of partonkTsmearing effects in direct photon production at the Fermilab Tevatron

Abstract: Previous detailed studies of direct photon production from both fixed-target and collider experiments have witnessed a pattern of deviation between the measured inclusive cross sections and the corresponding theoretical expectations in the low transverse momentum (p T ) regime. Most data sets display steeper p T dependence than the next-to-leading-order ͑NLO͒ perturbative QCD ͑PQCD͒ calculations with standard choices of scales and parton distribution functions in this region. A simple implementation of higher-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…The ZEUS fit to the data gave a k T value of about 1.7 GeV [3]. A similar situation is observed also at Tevatron energies: in order to describe the measured transverse momentum distributions of the photon the Gaussian-like k T spectrum with an average value of k T $ 3 GeV was introduced [9,10]. Of course, such large par-tonic k T must have a significant perturbative QCD component.…”
Section: Introductionsupporting
confidence: 59%
“…The ZEUS fit to the data gave a k T value of about 1.7 GeV [3]. A similar situation is observed also at Tevatron energies: in order to describe the measured transverse momentum distributions of the photon the Gaussian-like k T spectrum with an average value of k T $ 3 GeV was introduced [9,10]. Of course, such large par-tonic k T must have a significant perturbative QCD component.…”
Section: Introductionsupporting
confidence: 59%
“…At the leading order of perturbative Quantum Chromodynamics (pQCD), prompt photons can be produced via quark-gluon Compton scattering or quark-antiquark annihilation and so, the cross sections of these processes are strongly sensitive to the parton (quark and gluon) content of a proton 1 . The perturbative QCD calculations [11] in the next-to-leading order (NLO) approximation agree with the recent high-p T measurements [6] within uncertainties (see also discussions in [12][13][14][15][16]). However, there are still open questions.…”
Section: Introductionsupporting
confidence: 76%
“…Our approach is based on the k t -factorization scheme, which, unlike many early calculations [13,16], provides solid theoretical grounds for adequately taking into account the effects of initial parton momentum. The central part of our consideration is the off-shell gluon-gluon fusion subprocess g * + g * → γ + qq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite such a prospect, this process has been a mystery for a long time. Theories, even the next-to-leading order (NLO) calculations in Quantum Chromodynamics (QCD), could not reproduce measurement results, and intensive studies and debates were made to solve the problem (see, for example, [3,4] and the references therein). As higher energy collision data became available [5,6,7,8], it has been revealed that the photon production in high transverse momentum (p T ) regions ( 50 GeV) can be reasonably described by the NLO calculation [9], although discussions are yet to be conclusive for lower p T production.…”
Section: Introductionmentioning
confidence: 99%